Efficacy of soil amendment on seed germination, web blight intensity and yield of Frenchbean (Phaseolus vulgaris) - YADAV, B C; GUPTA, R P; SINGH, S K (The Indian Journal of Agricultural Sciences, 2026)
Web blight of Frenchbean (Phaseolus vulgaris L.) caused by Rhizoctonia solani Kühn is one of the most important disease. Experiment was conducted in field to find out the effect of soil amendment on seed germination, web blight intensity and yield of Frenchbean. Seed germination was maximum in neem oil cake (97.7%) amended soil followed by 93.1, 89.8, 86.1 and 82.1% germination in soil amended with mustard oil cake, mahua oil cake, linseed oil cake, saw dust as compared to non-amended soil (71.5%), respectively. Maximum disease control (43.6%) and green pod yield (62.4 q/ ha) were recorded in neem oil cake followed by mustard oil cake (35.2%, 57.0 q/ha), mahua oil cake (28.1%, 52.4 q/ha), linseed oil cake (26.6%, 51.3 q/ha), saw dust (19.6%, 36.8 q/ha) and unamended soil (0.0%, 36.9 q/ha), respectively.